The relationship between the leadership style of the director and the motivation of millennial generation teachers - Hernández Colón, Melissa (2021)
The purpose of this quantitative correlational research was to determine how the leadership style of the school principal relates to the work motivation of Millennials Generation employees. The theoretical framework that founded the research problem was the existentialist humanist theory of Ortega. The sample was made up of 176 participants from the Ponce region of the Puerto Rico Department of Education. To collect the data, the extrinsic and intrinsic motivation instrument, and the Leader Behavior Analysis II (LBAII) were used. From the data, a profile of the study participants was established. The main result showed that there is a significant relationship between the leadership style of the director and the motivation of the Millennials generation teachers.